The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1121/1.3273893
|View full text |Cite
|
Sign up to set email alerts
|

A computer model of auditory efferent suppression: Implications for the recognition of speech in noise

Abstract: The neural mechanisms underlying the ability of human listeners to recognize speech in the presence of background noise are still imperfectly understood. However, there is mounting evidence that the medial olivocochlear system plays an important role, via efferents that exert a suppressive effect on the response of the basilar membrane. The current paper presents a computer modeling study that investigates the possible role of this activity on speech intelligibility in noise. A model of auditory efferent proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 48 publications
7
87
0
7
Order By: Relevance
“…The relationship between estimated OHC gain reduction and elicitor level was nearly linear in the case of the Kawase et al data and for the present study, as shown in Figure 12A. Brown et al (2010) also predicted a linear relation between noise level and the efferent attenuation that maximized speech recognition. These results are consistent with OAE data suggesting a linear growth in MOCR strength (as estimated in units of percent of maximum OAE amplitude) with increased elicitor level (Backus and Guinan 2006).…”
Section: Bsupporting
confidence: 80%
See 3 more Smart Citations
“…The relationship between estimated OHC gain reduction and elicitor level was nearly linear in the case of the Kawase et al data and for the present study, as shown in Figure 12A. Brown et al (2010) also predicted a linear relation between noise level and the efferent attenuation that maximized speech recognition. These results are consistent with OAE data suggesting a linear growth in MOCR strength (as estimated in units of percent of maximum OAE amplitude) with increased elicitor level (Backus and Guinan 2006).…”
Section: Bsupporting
confidence: 80%
“…For the purpose of this study, the gain was controlled independently in a single pathway, since the relationship between elicitor level and amount of gain reduction is not known. A similar approach has been taken in several other modeling studies (e.g., Ferry and Meddis 2007;Ghitza et al 2007;Messing et al 2009;Brown et al 2010). Conditions will be labeled by the amount of OHC gain reduction (ΔG in dB) associated with the C OHC value.…”
Section: Auditory Nerve Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar method is employed in these experiments; however, in addition to simulating hearing impairment, MOC feedback was simulated by adjusting C OHC . This approach is similar to other modeling studies (Ferry and Meddis 2007;Ghitza et al 2007;Messing et al 2009;Brown et al 2010) that model the basic effect of the MOCR by reducing the amount of cochlear nonlinearity.…”
Section: Ohc Control In the Power Law Modelmentioning
confidence: 71%